Pain Clinic in Tibet, China: A Single-Center Retrospective Study - Le Shen; Xin Zhang; Dawawuzhu; Labaciren; Yuelun Zhang; Zhonghuang Xu; Yuguang Huang (Pain Research and Management)
Pain disease is a worldwide problem.The prevalence of chronic pain in developed and developing countries has been reported in some published research. However, little knowledge of situation of pain clinic in Tibet is known. Tibet Autonomous Region People’s Hospital established the first pain clinic in Tibet. This study collected and analyzed the data of medical records of pain clinic in Tibet Autonomous Region People’s Hospital from September 2017 to August 2018. The results showed that the total amounts of patients visiting pain clinic were very small, the most common pain diseases were postherpetic neuralgia and sciatica, and more female patients visited the pain clinic than male patients. All these results indicate that the hospital and government need to pay more attention to the development and promotion of pain medicine in Tibet to make Tibetans being accessed to high-quality pain clinic service.